Cutting performance evaluation of boron-doped and undoped diamond coatings in drilling of CFRP laminates. (April 2022) - Soldatov, Alexander; Okada, Akira; Ogawa, Hitoshi
This study investigated the effect of boron-doped and undoped diamond coatings on the cutting performance of cobalt cemented tungsten carbide (WC-Co) drills when drilling CFRP. Three types of diamond coating, as boron-doped microcrystalline (B-MCD), boron-doped nanocrystalline (B-NCD), and undoped nanocrystalline (NCD), were deposited on specially designed for drilling of CFRP one-shot drills by the hot filament chemical vapor deposition (HFCVD) method. The coating characteristics, such as surface morphology, roughness, carbon structure, and interfacial adhesion, were investigated. Then cutting tests were carried out, and the tool's flank wear, thrust force, and torque were evaluated. For comparison of cutting performance, non-coated WC-Co drills were used in the tests as well. Furthermore, drilled holes were inspected in terms of peel-up and push-out delamination. According to the results, the B-MCD coated drill presented advantages in tool life, and quality of drilled holes over the NCD and B-NCD coated drills. Also, the results confirmed the adhesion enhanced effect of diamond coating to WC-Co substrate through boron doping of the layer.